A Meta-Analysis of Correlations between Chronic Obstructive Pulmonary Disease, Smoking, and Severity of COVID-19 - Gigih Cita Pambudi; Setyo Sri Rahardjo; Sumardiyono Sumardiyono (Journal of Epidemiology and Public Health, 2021)
Background: Corona Virus Disease 2019 (COVID-19) is a respiratory disease that can progress to severe hypoxemia with cases reaching more than 235 million cases worldwide until November 2021. The association with Chronic Obstructive Pulmonary Disease (COPD) and smoking habits are both very common globally and may increase the severity of COVID-19. However, it has not been elucidated. Given the gaps in evidence and the increasing prevalence of COVID-19, this study aimed to examine the influence of COPD and smoking habits on the severity of COVID-19 patients.Subjects and Method: This meta-analysis study was conducted with PICO as follows: Popula